Maternal smoking cessation in the first trimester still poses an increased risk of attention-deficit/hyperactivity disorder and learning disability in offspring - Li, Qiu; Cai, Xiaotang; Zhou, Hui; Ma, Dan; Li, Na (Frontiers in Public Health, 2024)
Background Studies have found maternal smoking during pregnancy was linked to attention-deficit/hyperactivity disorder (ADHD) risk. It is unclear if maternal smoking cessation during pregnancy lowers ADHD and learning disability (LD) risk in offspring. This study aimed to explore the associations between maternal smoking cessation during pregnancy and ADHD and LD risk in offspring. Methods Data from the National Health and Nutrition Examination Survey 1999–2004 (8,068 participants) were used. Logistic regression was used to analyze the associations between maternal smoking and smoking cessation during pregnancy and ADHD and LD risk in offspring. Results Compared to non-smokers’ offspring, maternal smoking during pregnancy increased the risk of ADHD (odds ratios [OR] = 2.07, 95% confidence interval [CI]: 1.67–2.56) and LD (OR = 1.93, 95% CI: 1.61–2.31) in offspring, even if mothers quit smoking later (ORADHD = 1.91, 95%CIADHD: 1.38–2.65, ORLD = 1.65, 95%CILD: 1.24–2.19). Further analysis of the timing of initiation of smoking cessation during pregnancy revealed that, compared to non-smokers’ offspring, maternal quitting smoking in the first trimester still posed an increased risk of ADHD (OR = 1.72, 95% CI: 1.41–2.61) and LD (OR = 1.52, 95% CI: 1.06–2.17) in offspring. Maternal quitting smoking in the second or third trimester also had a significantly increased risk of ADHD (OR = 2.13, 95% CI: 1.26–3.61) and LD (OR = 1.82, 95% CI: 1.16–2.87) in offspring. Furthermore, maternal smoking but never quitting during pregnancy had the highest risk of ADHD (OR = 2.17, 95% CI: 1.69–2.79) and LD (OR = 2.10, 95% CI: 1.70–2.58) in offspring. Interestingly, a trend toward a gradual increase in the risk-adjusted OR for ADHD and LD risk was observed among the three groups: maternal quitting smoking in the first trimester, maternal quitting smoking in the second or third trimester, and maternal smoking but never quitting. Conclusion Maternal smoking cessation in the first trimester still poses an increased risk of ADHD and LD in offspring. Furthermore, it seems that the later the mothers quit smoking during pregnancy, the higher the risk of ADHD and LD in their offspring. Therefore, early intervention of maternal smoking in preconception and prenatal care is vital for offspring neurodevelopment.